CORPORATE ENVIRONMENTAL DISCLOSURE, ENVIRONMENTAL PERFORMANCE, AND CORPORATE GOVERNANCE STRUCTURES ON FIRM VALUE - Kenny Ardillah; Zelindio Chandra (Universitas Multimedia Nusantara, 2021)
Abstract - Each company seeks to increase the value to increase shareholder prosperity by implementing operations that pay attention to social and environmental aspects. This research aims to prove the effect of corporate environmental disclosure, environmental performance, and corporate governance structure (managerial ownership and audit committee) on firm value. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019 as many as 141 companies. Sample The sampling method used in this study was purposive sampling with a total sample of 17 companies with 85 data. The data analysis method in this study used multiple linear regression with an alpha significance level of 5%. The results showed that the company's environmental disclosure and environmental performance had a significant positive effect on firm value. On the other hand, corporate governance structures such as audit committees do not affect firm value, and managerial ownership significantly affects firm value. From this research, investors can be more relevant to choosing investment decisions wisely and describing the company's financial and non-financial conditions according to the firm value inside and outside the company. Keywords: Audit Committee; Corporate Environmental Disclosure; Environmental Performance; Firm Value; Managerial Ownership